Memory Susceptibility to Retroactive Interference Is Developmentally Regulated by NMDA Receptors - Ge, Minyan; Song, Huina; Li, Hua; Li, Ranran; Tao, Xiaoqing; Zhan, Xu; Yu, Nana; Sun, Ning; Lu, Youming; Mu, Yangling (Cell reports (Cambridge), 2019)
Retroactive interference (RI) occurs when new incoming information impairs an existing memory, which is one of the primary sources of forgetting. Although long-term potentiation (LTP) reversal shows promise as the underlying neural correlate, the key molecules that control the sensitivity of memory circuits to RI are unknown, and the developmental trajectory of RI effects is unclear. Here we found that depotentiation in the hippocampal dentate gyrus (DG) depends on GluN2A-containing NMDA receptors (NMDARs). The susceptibility of LTP to disruption progressively increases with the rise in the GluN2A/GluN2B ratio during development. The vulnerability of hippocampus-dependent memory to interference from post-learning novelty exploration is subject to similar developmental regulation by NMDARs. Both GluN2A overexpression and GluN2B downregulation in the DG promote RI-induced forgetting. Altogether, our results suggest that a switch in GluN2 subunit predominance may confer age-related differences to depotentiation and underlie the developmental decline in memory resistance to RI. [Display omitted] •LTP in the dentate gyrus becomes more readily reversible during development•The age dependence of depotentiation is controlled by the GluN2A/GluN2B subunit ratio•The developmental enhancement of LTP reversal is associated with increased forgetting•Changes in the GluN2A/GluN2B subunit ratio affect rates of forgetting Ge et al. report that the NMDA receptor GluN2A/GluN2B subunit ratio determines the sensitivity of strengthened neuronal connections to depotentiation. As the ratio rises during development, memories become more vulnerable to disruption by post-learning interference. These findings help to illuminate the mechanism by which forgetting rates may vary with age.